2001
DOI: 10.1016/s0885-3924(01)00357-8
|View full text |Cite
|
Sign up to set email alerts
|

Epoetin Alfa in Cancer Patients

Abstract: Anemia is a common cause of cancer-related fatigue. A systematic review of the literature was performed to establish guidelines on the use of epoetin alfa for the treatment of anemia. The evidence in support of these guidelines was selected, reviewed, and summarized by the members of the Canadian Cancer and Anemia Guidelines Development Group. The effects of epoetin alfa on quality of life (QOL) in patients with cancer were examined in 5 randomized, placebo-controlled trials and 2 large, open-label, nonrandomi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2002
2002
2021
2021

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(3 citation statements)
references
References 29 publications
0
3
0
Order By: Relevance
“…In a recent systematic review originally prepared for the Cochrane Library, Bohlius and colleagues showed that while the administration of erythropoietin is clearly associated with significant increases in hemoglobin, the evidence that it also reduces fatigue is inconclusive [10]. This is in keeping with our clinical observations that the correction of the anemia with administration of erythropoietin according to evidence practice guidelines [70] or of Packed Red Cells rarely ameliorates fatigue to the degree intended. This finding suggests that other stressors experienced by individuals with advanced cancer also contribute to fatigue.…”
Section: Introductionmentioning
confidence: 65%
“…In a recent systematic review originally prepared for the Cochrane Library, Bohlius and colleagues showed that while the administration of erythropoietin is clearly associated with significant increases in hemoglobin, the evidence that it also reduces fatigue is inconclusive [10]. This is in keeping with our clinical observations that the correction of the anemia with administration of erythropoietin according to evidence practice guidelines [70] or of Packed Red Cells rarely ameliorates fatigue to the degree intended. This finding suggests that other stressors experienced by individuals with advanced cancer also contribute to fatigue.…”
Section: Introductionmentioning
confidence: 65%
“…11 Available evidence supports the correlation between anemia and fatigue. 25,26 Chemotherapy drugs that cross the blood-brain barrier may induce neurotoxicities that produce fatigue. 24 Most patients experience fluctuations in fatigue during high-dose chemotherapy paired with stem cell transplantation, with fatigue increasing as the patients’ blood counts approach white blood cell nadir but improving as counts recover.…”
Section: Clinical Correlates Of Cancer-related Fatiguementioning
confidence: 99%
“…Studies have focused on understanding the factors that contribute to CRF, the treatment received, and a variety of chronic physical or psychological comorbid conditions (Wang, 2008). Some studies have stated that anemia and accumulation of end products from cell destruction causes fatigue (Turner et al, 2001;Demetri et al, 1998). It was seen that chemotherapy drugs that cross the blood-brain barrier might induce neurotoxicities which can produce fatigue (Smets et al, 1993).…”
Section: Resultsmentioning
confidence: 99%